Об устройствах для определения магнитных моментов габаритных объектов техники - Гринченко, Владимир Сергеевич; Ерисов, Анатолий Васильевич (НТУ "ХПИ", 2010)
Приведены результаты анализа устройства для измерения магнитного момента габаритных объектов техники, основанного на способе прямых измерений магнитного потока. Определены требования к выполнению первичного преобразователя этого устройства. Предложен способ синтеза сложных систем первичных преобразователей.

Analysis of a device for measuring magnetic moments in largedimensioned technical objects is made on the basis of direct measurements of magnetic flux. Requirements for design of the device’s primary converter are specified. A technique for complex primary converter systems synthesis is introduced.
About device for testing magnetic moments in large-dimensioned technical objects
Keywords: высокоточные устройства измерения; определение магнитных моментов; синтез сложных систем; космические аппараты; large-dimensioned technical objects; magnetic moment; measurements; primary converters; synthesis